1999
DOI: 10.1007/s002800050907
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interactions of a new derivative of spicamycin, KRN5500, and other anticancer drugs using a three-dimensional model

Abstract: These results suggest the usefulness of combinations of KRN5500 with cisplatin, carboplatin or etoposide for chemotherapy for non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…In this method, synergy, additivity, and antagonism are defined as combination effect > 0, combination effect = 0, and combination effect < 0, respectively. The theoretical basis and practical application of the Kanzawa method have been previously described (4,9). Briefly, cytotoxicity data in an 8 Â 8 well matrix format from six replicate plates were entered into a Microsoft Excel (Redmond, WA) spreadsheet and the combination effect was computed.…”
Section: Methodsmentioning
confidence: 99%
“…In this method, synergy, additivity, and antagonism are defined as combination effect > 0, combination effect = 0, and combination effect < 0, respectively. The theoretical basis and practical application of the Kanzawa method have been previously described (4,9). Briefly, cytotoxicity data in an 8 Â 8 well matrix format from six replicate plates were entered into a Microsoft Excel (Redmond, WA) spreadsheet and the combination effect was computed.…”
Section: Methodsmentioning
confidence: 99%
“…The three-dimensional method of Kanzawa et al 15,48 was used to obtain a global view of the interaction of fludarabine phosphate and DETA-NO in a representative patient. (a) The mean combination effect surface from four separate determinations reveals a continuum of response from highly antagonistic (light) to highly synergistic (dark).…”
Section: Figurementioning
confidence: 99%
“…Gemcitabine in combination with cisplatin has been shown to have either an additive or a synergistic effect in vitro and in vivo in a number of different tumor systems (27)(28)(29)(30). Similarly, treatment with gemcitabine with vindesine was shown to have a synergistic cytotoxic effect when used against a lung cancer cell line (31). Clinical trials of gemcitabine with carboplatin and paclitaxel have shown promising results in patients with non-small cell lung cancer (32).…”
Section: + +mentioning
confidence: 99%
“…With phosphorylation, blocked iKBa remains intact, thereby, blocking NF-KB translocation to the nucleus and subsequent activation of antiapoptotic genes that cause TNF-a insensitivity, thereby allowing the cells to proceed through apoptosis. This iKBa "super-repressor" has also been shown to induce apoptosis in other systems (31,32). The "super-repressor" produces constitutive repression of NF-KBdirected transcription, despite the presence of agonists that normally induce the degradation of iKBa and the nuclear translocation of NF-KB (24).…”
Section: Introduction Introductionmentioning
confidence: 99%